A high-zirconium refractory material and its preparation method and application
By designing multi-layer structure and gradient Al2O3 content in high zirconium refractory materials, combined with wet ball milling and sintering technology, the cracks and pore problems in the preparation of high zirconium refractory bricks are solved, and the thermal shock resistance and glass liquid corrosion resistance are improved. Extend the service life of the kiln.
Patent Information
- Application Number
- CN202411288423.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Existing high-zirconium refractory bricks are prone to cracks and pores during the preparation process, resulting in low yield and poor thermal shock resistance, which affects the life of the glass kiln and the quality of the glass kiln.
High zirconium refractory material with multi-layer structure, the surface layer, intermediate layer and transition layer all contain ZrO2 and Al2O3. The Al2O3 content is optimized through gradient design, combined with wet ball milling and sintering technology, and a high toughness, bending strength and excellent resistance are prepared. Materials with thermal shock properties.
It significantly improves the mechanical properties and thermal shock resistance of the material, reduces glass-liquid corrosion damage, extends the service life of the kiln, and maintains the resistance to glass-liquid corrosion of zirconia.
Smart Images

Figure CN118791301B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high temperature resistant materials, and in particular to a high zirconium refractory material and a preparation method and application thereof. Background Art
[0002] Zirconia is one of the key refractory materials that can come into direct contact with molten glass and is widely used in various glass kilns due to its excellent properties such as high temperature resistance, high mechanical strength, corrosion resistance and low pollution.
[0003] At present, high-zirconium refractory bricks prepared by the melt-casting method are widely used in the market, that is, melt-cast bricks with a zirconium oxide content of more than 85wt%. However, since the preparation of high-zirconium refractory bricks involves a melting and cooling process, the cooling rate is relatively fast, resulting in cracks easily appearing in the products and a high porosity content, so the yield is extremely low and the product price remains high. In addition, since zirconium oxide has a high thermal expansion coefficient and low thermal conductivity, its thermal shock resistance is poor. When subjected to thermal shock and uneven heating, it is very easy to crack, resulting in cracking and peeling, which damages the structure of the glass melting pool wall bricks and affects the life of the glass kiln and the quality of the glass.
[0004] Therefore, there is an urgent need to develop a refractory material for glass furnaces that has good resistance to glass liquid erosion and excellent thermal shock resistance. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a high-zirconium refractory material for a glass melting pool having high toughness, high strength, high thermal shock stability and resistance to glass liquid corrosion, and a preparation method thereof.
[0006] The specific content of the invention is as follows:
[0007] In a first aspect, the present invention provides a high-zirconium refractory material, the high-zirconium refractory material comprising a surface layer, an intermediate layer, and a transition layer between the intermediate layer and the surface layer, wherein the surface layer, the intermediate layer and the transition layer all contain ZrO 2 and Al 2 O 3 ;in,
[0008] In the surface layer, Al 2 O 3 The volume fraction is 0<V(Al 2 O 3 )≤10 vol%;
[0009] In the intermediate layer, Al 2 O 3 The volume fraction is 20 vol%<V(Al 2 O 3 )<30 vol%;
[0010] In the transition layer, Al 2 O 3 The volume fraction is 15vol%<V(Al 2 O 3 )<20 vol%.
[0011] Optionally, the transition layer is a multi-layer structure, in which the Al 2 O 3 The content increases gradually from the surface to the middle layer.
[0012] Optionally, the number of layers of the multilayer structure is 1≤n≤4.
[0013] Optionally, in the multilayer structure, the ratio of the thickness of the nth layer to the thickness of the n-1th layer is 0.9-1.1.
[0014] Optionally, the thickness of the surface layer is 10%-30% of the total thickness of the high-zirconium refractory material;
[0015] The thickness of the intermediate layer is 15%-25% of the total thickness of the high zirconium refractory material.
[0016] Optionally, the high-zirconium refractory material has a relative density of ≥98%, an open porosity of ≤0.4%, a bending strength of ≥600 MPa, and a critical thermal shock resistance temperature difference of ≥600°C.
[0017] In a second aspect, the present invention provides a method for preparing the high zirconium refractory material according to the first aspect, the preparation method comprising:
[0018] ZrO 2 -Al 2 O 3 Preparation of composite powders: Multiple groups of ZrO 2 -Al 2 O 3 The composite powder is wet-milled, dried and sieved to obtain the powder required for forming the surface layer, middle layer and transition layer of the high-zirconium refractory material;
[0019] Molding and sintering: The powder is filled into a mold by layer-by-layer powder spreading, and then sintered without pressure by cold isostatic pressing; or, the powder is filled into a mold and sintered by hot pressing to obtain a dense ZrO 2 -Al 2 O 3 Gradient symmetrical structure refractory material.
[0020] Optionally, the liquid medium used in the wet ball milling is composed of a mixture of a polyvinyl alcohol solution and anhydrous ethanol; wherein the volume proportion of the polyvinyl alcohol solution is 10-30 vol%; the amount of the polyvinyl alcohol is 0.5% to 1.5% of the weight of the composite powder;
[0021] The wet ball milling process has a ball milling time of 10-18 h and a rotation speed of 100-200 r / min.
[0022] Optionally, the cold isostatic pressing pressure is 200-400 Mpa, and the holding time is 2-5 min;
[0023] The pressureless sintering temperature is 1550-1750°C, and the holding time is 2-4 hours;
[0024] The hot pressing sintering pressure is 30-70 MPa, the temperature is 1450-1700°C, and the heat preservation and pressure holding time is 1-3 h.
[0025] In a third aspect, the present invention provides an application of the high-zirconium refractory material described in the first aspect, comprising: using the high-zirconium refractory material for preparing a glass melting pool.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] The present invention provides a high-zirconium refractory material, which comprises a surface layer, an intermediate layer, and a transition layer between the intermediate layer and the surface layer, wherein the surface layer, the intermediate layer and the transition layer all contain ZrO 2 and Al 2 O 3 ; Wherein, in the surface layer, Al 2 O 3 The volume fraction is 0<V(Al 2 O 3 )≤10 vol%; in the intermediate layer, Al 2 O 3 The volume fraction is 20 vol%<V(Al 2 O 3 )<30 vol%; in the transition layer, Al 2 O 3 The volume fraction is 15vol%<V(Al 2 O 3 )<20vol%.
[0028] The high-zirconium refractory material provided by the present invention is used as a raw material for preparing a glass kiln, and has excellent mechanical properties, thermal shock resistance, and resistance to erosion by molten glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 A schematic diagram of the structure of a high-zirconium refractory material provided in an embodiment of the present invention is shown;
[0031] Figure 2 A flow chart of a method for preparing a high-zirconium refractory material provided by an embodiment of the present invention is shown;
[0032] Figure 3 The cross-sectional SEM of the high-zirconium refractory material provided by the embodiment of the present invention is shown;
[0033] Figure 4 The cross-sectional SEM image of the high zirconium refractory material provided by the embodiment of the present invention after being corroded at 1500°C for 4 hours is shown;
[0034] Figure 5 The EDS surface scanning result diagram of Zr, Y and Si elements in the cross section of the high zirconium refractory material provided by the embodiment of the present invention after being corroded at 1500°C for 4 hours is shown;
[0035] Figure 6 The figure shows the EDS element analysis result of the cross section of the high zirconium refractory material provided by the embodiment of the present invention after being corroded at 1500°C for 4 hours.
[0036] Description of reference numerals:
[0037] D 0 , middle layer; D 1 , surface; D 2 , transition layer. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.
[0039] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0040] Technologies, methods, and apparatus known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, such technologies, methods, and apparatus should be considered part of the authorization specification.
[0041] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0042] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0043] It should be noted that the composition of the high zirconium refractory material provided by the present invention is ZrO 2 and Al 2 O 3 , among which ZrO 2 Refers to Y-stabilized ZrO 2 The specific implementation contents of the present invention are as follows:
[0044] In the first aspect, the present invention provides a high zirconium refractory material, see Figure 1 The schematic diagram of the structure of the high zirconium refractory material shown in FIG. 1 、Middle layer D 0 , and located in the middle layer D 0 and surface D 1 The transition layer D 2 , where the surface D 1 、Middle layer D 0 With transition layer D 2 The composition of 2 and Al 2 O 3 Surface D 1 In, Al 2 O 3 The volume fraction is 0<V(Al2 O 3 )≤10 vol%; middle layer D 0 In, Al 2 O 3 The volume fraction is 20 vol%<V(Al 2 O 3 )<30 vol%; due to zirconium oxide (ZrO 2 ) and aluminum oxide (Al 2 O 3 )Difference in thermal expansion coefficient of materials. As the content of aluminum oxide increases, the surface D 1 and the middle layer D 0 The difference in linear expansion coefficient will gradually increase during the sintering process. 2 O 3 The middle layer D 0 Shrinkage strength is less than that of the surface layer with high zirconium content D 1 Therefore, the surface layer D of the gradient material 1 Tensile stress will be generated, and compressive stress will exist inside the material; if the stress value is too large, it will damage the material structure (for example, the surface D 1 Therefore, the present invention provides a method for forming a crack or a layer of cracks in the surface layer D 1 and the middle layer D 0 Set up a transition layer D between 2 , transition layer D 2 In, Al 2 O 3 The volume fraction is 15vol%<V(Al 2 O 3 )<20 vol%;With the help of the transition layer, the stress value can be optimized to the minimum; In addition, the existence of internal compressive stress in the material can reduce the stress at the crack tip. At the same time, with the release of stress, it will promote the phase transformation of metastable tetragonal zirconia and promote the phase transformation toughening effect; At the same time, due to the existence of the interlayer interface, the crack will be blocked, absorbed, scattered, and induced by the interface, reducing the energy at the crack tip and causing the crack to deflect, extending the crack propagation path. Therefore, on the basis of the phase transformation toughening of zirconia and the dispersion strengthening of the second phase alumina particles, the residual stress caused by the layered structure of the gradient material and the toughening effect of the interface characteristics effectively improve the thermal shock resistance of the material.
[0045] In addition, the present invention optimizes the number of layers, layer thickness and composition of each layer to enable the material to have the minimum thermal stress and the optimal stress gradient, thus having excellent comprehensive performance (relative density ≥ 98%, open porosity ≤ 0.4%, bending strength ≥ 600 Mpa, critical thermal shock resistance temperature difference ≥ 600 ℃). 2 It is a multi-layer structure, and the transition layer D can be2 Set to d 1 (Close to D 0 ), d 2 , d 3 …d n layer, but d n :d n-1 The thickness ratio of the layer should be 0.9-1.1, where 1≤n≤4; transition layer D 2 In the surface layer, the aluminum oxide content increases with the 1 To the middle layer D 0 The direction increases with gradient; the middle layer D 0 The thickness of the high zirconium refractory material is 15%-25% of the total thickness; the surface layer D 1 The thickness is 10%-30% of the total thickness of the high zirconium refractory material.
[0046] In a second aspect, the present invention provides a method for preparing a high-zirconium refractory material. Figure 2 The flowchart of the preparation method of the high zirconium refractory material provided by the embodiment of the present invention is shown as follows: Figure 2 As shown, the preparation method of high zirconium refractory material includes ZrO 2 -Al 2 O 3 The preparation, molding and sintering of the composite powder specifically include the following steps:
[0047] S1. Multiple groups of ZrO with different ratios 2 -Al 2 O 3 The composite powder is wet-milled, dried and sieved to obtain the powder required for forming the surface layer, middle layer and transition layer of the high-zirconium refractory material;
[0048] In specific implementation, among the powders required for the surface layer, Al 2 O 3 The volume fraction is 0<V(Al 2 O 3 )≤10 vol%; Among the powders required for the intermediate layer, Al 2 O 3 The volume fraction is 20 vol%<V(Al 2 O 3 )<30 vol%; Among the powders required for the transition layer, Al 2 O 3 The volume fraction is 15vol%<V(Al 2 O 3 )<20 vol%. Furthermore, the transition layer can be further gradient-designed into a multilayer structure according to actual use conditions. 2 -Al 2 O 3In the composite powder, Al 2 O 3 The volume proportion of Al 2 O 3 The content increases gradually from the surface layer to the middle layer. In this way, due to the existence of the interlayer interface, the crack will be blocked, absorbed, scattered, induced, etc. by the interface, reducing the energy at the crack tip and causing the crack to deflect, extending the crack propagation path. Therefore, on the basis of the zirconia phase transformation toughening and the second phase alumina particle dispersion strengthening, the residual stress caused by the layered structure of the gradient material and the toughening effect of the interface characteristics effectively improve the thermal shock resistance of the material.
[0049] S2, the powder is filled into a mold by layer-by-layer powder spreading method, and then pressureless sintering is performed after forming by cold isostatic pressing; or, the powder is filled into a mold and sintered by hot pressing sintering to obtain a dense ZrO 2 -Al 2 O 3 Gradient symmetrical structure refractory material.
[0050] In the specific implementation, when the pressureless sintering method is adopted, the powder is filled in the mold, and the prefabricated body is obtained under the action of cold isostatic pressing of 200-400 MPa and the holding time is 2-5 min. The prefabricated body is placed at 1550-1750 ° C and pressureless sintered for 2-4 h to obtain a dense ZrO 2 -Al 2 O 3 Gradient symmetrical structure refractory material; when hot pressing sintering is adopted, the pressure is controlled at 30-70 Mpa, the temperature is 1450-1700 ℃, and the heat and pressure are maintained for 1-3 h to obtain a dense ZrO 2 -Al 2 O 3 Gradient symmetrical structure refractory material.
[0051] In some embodiments, the liquid medium used for wet ball milling consists of a polyvinyl alcohol solution and anhydrous ethanol; wherein the volume ratio of the polyvinyl alcohol solution is 10-30 vol%; the amount of polyvinyl alcohol is 0.5% to 1.5% of the weight of the composite powder; the wet ball milling time is 10-18 h, and the rotation speed is 100-200 r / min.
[0052] In a third aspect, the present invention provides an application of the high-zirconium refractory material described in the first aspect, comprising: using the high-zirconium refractory material for preparing a glass melting pool.
[0053] The present invention combines the structural design concept of symmetry + gradient to provide a high-zirconium refractory material. The high zirconium content layer on the surface can maintain the excellent glass liquid corrosion resistance of the zirconia material; the aluminum-rich content layer in the middle layer uses the addition of the second phase aluminum oxide to reduce the thermal expansion coefficient of the zirconia material and improve the thermal conductivity of the material, thereby optimizing the thermal shock resistance of the composite material; the layered gradient layer between the surface layer and the middle layer can minimize the stress gradient, reduce the residual stress of the material, and thus reduce structural defects; the symmetrical structural design can keep the shrinkage rate of each layer of the material synchronized during the sintering process to avoid warping of the material. As a high-zirconium refractory material for glass melting pools, it can reduce the thermal expansion coefficient and improve the thermal conductivity, improve the thermal shock resistance, and use the gradient interface layered structure to improve the mechanical properties, while maintaining the excellent glass liquid corrosion resistance of the zirconia material.
[0054] In order to enable those skilled in the art to more clearly understand the present invention, a high-zirconium refractory material and a preparation method and application thereof according to the present invention are now described in detail through the following examples.
[0055] Example 1
[0056] (1) ZrO 2 -Al 2 O 3 Preparation of composite powder
[0057] Different ratios of ZrO 2 -Al 2 O 3 The composite powder was ball-milled by liquid phase method, the ball-milling time was 12 h, the rotation speed was 120 r / min, the liquid medium was 20 vol% polyvinyl alcohol solution and 80 vol% anhydrous ethanol, wherein the amount of polyvinyl alcohol was 0.8% of the weight of the composite powder; after ball-milling, the powder was dried and sieved to obtain the powder required for each layer of the gradient material;
[0058] The composition of each layer of powder is:
[0059] Surface D 1 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction should be 10 vol%.
[0060] Middle layer D 0 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction is 25 vol%.
[0061] Gradient transition layer D 2 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction is 17 vol%.
[0062] In this embodiment, D 2 The layer is set to 1, that is, n=1.
[0063] (2) Material forming and sintering
[0064] The powders required for each layer involved in (1) are spread layer by layer, combined with cold isostatic pressing at 300 MPa for 3 minutes to obtain a prefabricated embryo;
[0065] The thickness of each layer is: surface layer D 1 The thickness of the middle layer D is 17% of the total thickness. 0 The thickness of the gradient transition layer D is 22% of the total thickness. 2 The thickness is 22% of the total thickness.
[0066] The preform was sintered without pressure at 1700 °C for 2 h to obtain a dense ZrO 2 -Al 2 O 3 Gradient symmetrical structure refractory material, the relative density of this material is about 98%, the open porosity is about 0.38%, the bending strength is about 660 Mpa, and the critical thermal shock resistance temperature difference is about 700-800 ℃.
[0067] Example 2
[0068] (1) ZrO 2 -Al 2 O 3 Preparation of composite powder
[0069] Different ratios of ZrO 2 -Al 2 O 3 The composite powder was ball-milled by liquid phase method, the ball-milling time was 12 h, the rotation speed was 120 r / min, the liquid medium was 20 vol% polyvinyl alcohol solution and 80 vol% anhydrous ethanol, wherein the amount of polyvinyl alcohol was 0.8% of the weight of the composite powder; after ball-milling, the powder was dried and sieved to obtain the powder required for each layer of the gradient material;
[0070] The composition of each layer of powder is:
[0071] Surface D 1 The composition is ZrO 2 and Al2 O 3 , where Al 2 O 3 The volume fraction should be 10 vol%.
[0072] Middle layer D 0 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction is 25 vol%.
[0073] Gradient transition layer D 2 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction is 17 vol%.
[0074] In this embodiment, D 2 The layer is set to 1, that is, n=1.
[0075] (2) Material forming and sintering
[0076] The powders required for each layer involved in (1) were placed in the mold layer by layer, and hot pressed and sintered at 1550 °C for 2 h under a pressure of 45 MPa to obtain a dense ZrO 2 -Al 2 O 3 Gradient symmetrical structure refractory material, the relative density of this material is about 99%, the open porosity is about 0.28%, the bending strength is about 750 Mpa, and the critical thermal shock resistance temperature difference is about 700-800℃.
[0077] The thickness of each layer is: surface layer D 1 The thickness of the middle layer D is 17% of the total thickness. 0 The thickness of the gradient transition layer D is 22% of the total thickness. 2 The thickness is 22% of the total thickness.
[0078] Example 3
[0079] (1) ZrO 2 -Al 2 O 3 Preparation of composite powder
[0080] Different ratios of ZrO 2 -Al 2 O 3The composite powder was ball-milled by liquid phase method, the ball-milling time was 12 h, the rotation speed was 120 r / min, the liquid medium was 20 vol% polyvinyl alcohol solution and 80 vol% anhydrous ethanol, wherein the amount of polyvinyl alcohol was 0.8% of the weight of the composite powder; after ball-milling, the powder was dried and sieved to obtain the powder required for each layer of the gradient material;
[0081] The composition of each layer of powder is:
[0082] Surface D 1 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction should be 10 vol%.
[0083] Middle layer D 0 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction is 25 vol%.
[0084] Gradient transition layer D 2 Medium, d 1 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction is 19 vol% d 2 The composition is ZrO 2 and Al 2 O 3 , where Al 2 O 3 The volume fraction is 17 vol%.
[0085] In this embodiment, D 2 The number of layers is set to 2, that is, n=2.
[0086] (2) Material forming and sintering
[0087] The powders required for each layer involved in (1) are spread layer by layer, combined with cold isostatic pressing at 300 MPa for 3 minutes to obtain a prefabricated embryo;
[0088] The thickness of each layer is: surface layer D 1 The thickness of the middle layer D is 17% of the total thickness. 0 The thickness of the gradient transition layer D is 14% of the total thickness. 2 Medium 1The thickness is 13% of the total thickness, d 2 The thickness is 13% of the total thickness.
[0089] The preform was sintered without pressure at 1650℃ for 3 h to obtain a dense ZrO 2 -Al 2 O 3 Gradient symmetrical structure refractory material, the relative density of this material is about 98%, the open porosity is about 0.35%, the bending strength is about 680 Mpa, and the critical thermal shock resistance temperature difference is about 700-800℃.
[0090] Comparative Example 1
[0091] Using the surface layer D of the embodiment 1 The same material composition, the preparation of ZrO 2 -10 vol% Al 2 O 3 The other process parameters are the same as those in the embodiment to obtain ZrO 2 -10 vol% Al 2 O 3 Single-layer composite material, the relative density of this material is about 97.8%, the open porosity is about 1.2%, the flexural strength is about 450 Mpa, and the critical thermal shock resistance temperature difference is about 500-600℃.
[0092] Experimental Example (The refractory materials obtained from Example 1 and Comparative Example 1 were selected to perform the following performance tests)
[0093] (1) Microstructure and mechanical properties
[0094] Figure 3 The cross-sectional SEM of the high zirconium refractory material provided by the embodiment of the present invention is shown. Figure 3 (a) is a cross-sectional SEM of the high zirconium refractory material provided in Comparative Example 1, Figure 3 (b) is a cross-sectional SEM of the high zirconium refractory material provided in Example 1. It can be seen that the interlayer interface of the high zirconium refractory material provided in the embodiment of the present invention is obvious and has good interface bonding. There are a small number of closed pores inside the material, and there are no obvious defects such as interlayer cracks. According to the national standard GB / T25995-2010, the density and open porosity of the sample were measured by the Archimedes drainage method. The results showed that the density of both reached more than 97%. The three-point bending method was used to analyze the flexural strength of the material, and it was found that ZrO 2 -Al 2 O 3 The bending strength of the gradient material can reach 660 Mpa, which is higher than that of ZrO 2 -Al 2 O 3 The single-layer composite material (450 MPa) increased by about 46%.
[0095] (2) Thermal shock resistance
[0096] The water quenching method is used to test the thermal shock resistance, that is, the sample to be tested is placed in a muffle furnace, heated to 400, 600, and 800°C for 10 minutes, then taken out and placed in running water at room temperature for water quenching. The operation is repeated twice. After the sample is cooled and dried, the critical thermal shock resistance temperature difference of the material is determined based on the residual strength of the sample to determine the thermal shock resistance of the sample.
[0097] Under different thermal shock temperature differences, the ZrO 2 -Al 2 O 3 The residual strength of the gradient material after thermal shock test was analyzed. It was found that when the thermal shock temperature difference was lower than 600℃, the strength of the material did not decrease significantly. When the thermal shock temperature difference was 700-800℃, the residual strength of the gradient material dropped suddenly by about 300-400 Mpa. This indicates that the critical thermal shock resistance temperature difference of the material is 800℃, which is lower than that of ZrO 2 -Al 2 O 3 The critical thermal shock resistance temperature difference of the single-layer composite material is increased by about 200℃.
[0098] (3) Anti-corrosion performance of glass liquid
[0099] A high-temperature thermal simulation erosion experiment was used to study the sample's resistance to glass liquid erosion. The surface of the test sample was covered with glass powder and placed in a muffle furnace. It was heated to 1500 ℃ and kept warm for 4 h. After cooling with the furnace, a scanning electron microscope (SEM) combined with energy spectrum analysis (EDS) was used to analyze the corrosion of the sample.
[0100] Figure 4 The cross-sectional SEM image of the high zirconium refractory material provided by the embodiment of the present invention after being corroded at 1500°C for 4 hours is shown. Figure 5 The EDS surface scan result of Zr, Y and Si elements in the cross section of the high zirconium refractory material provided by the embodiment of the present invention after being eroded at 1500°C for 4 hours is shown; wherein, Figure 5 (a) shows the EDS surface scan result of Si element. Figure 5 (b) EDS surface scan result of Zr element. Figure 5 (c) EDS surface scan result diagram of element Y; Figure 6 The figure shows the EDS element analysis result of the cross section of the high zirconium refractory material provided by the embodiment of the present invention after being corroded at 1500°C for 4 hours; Figure 4-6 It can be seen that the ZrO provided in Example 1 2 -Al 2 O 3The gradient material is in close contact with the glass liquid, and the interface between the two is smooth, with no obvious erosion layer. The EDS surface scan results show that there is no obvious diffusion of Zr and Si elements, and the boundary line of element distribution between the glass phase and the gradient material is clearly visible. In addition, the content of the stabilizer Y element in the zirconium oxide raw material powder in the glass liquid is low, indicating that the dissolution of the Y element in the glass liquid is limited. 2 -Al 2 O 3 Cross-sectional SEM image of single-layer composite material and EDS surface scanning result image and Figure 4 , Figure 5 The above results show that the prepared gradient material has excellent resistance to glass erosion. 2 -Al 2 O 3 Compared with single-layer composite materials, it has the same anti-glass liquid erosion effect.
[0101] In summary, ZrO 2 -Al 2 O 3 Gradient materials compared to ZrO 2 -Al 2 O 3 Single-layer composite materials have the same resistance to glass liquid corrosion, but ZrO 2 -Al 2 O 3 Gradient materials have better mechanical properties and thermal shock resistance. The refractory brick materials used in glass kilns can effectively improve the service life of the kiln.
[0102] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.
[0103] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.
[0104] The above is a detailed introduction to a high-zirconium refractory material and its preparation method and application provided by the present invention. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A high zirconium refractory material, characterized in that: The high-zirconium refractory material comprises a surface layer, an intermediate layer, and a transition layer between the intermediate layer and the surface layer, wherein the surface layer, the intermediate layer and the transition layer are all ZrO2 and Al2O3; wherein, In the surface layer, the volume fraction of Al2O3 is 0<V(Al2O3)≤10 vol%; In the intermediate layer, the volume fraction of Al2O3 is 20 vol%<V(Al2O3)<30 vol%; In the transition layer, the volume fraction of Al2O3 is 15vol%<V(Al2O3)<20vol%; The transition layer is a multi-layer structure, and in the transition layer, the Al2O3 content increases gradually from the surface layer to the middle layer; The number of layers of the multilayer structure is 2≤n≤4; In the multilayer structure, the ratio of the thickness of the nth layer to the thickness of the n-1th layer is 0.9-1.1; The thickness of the surface layer is 10%-30% of the total thickness of the high zirconium refractory material; The thickness of the intermediate layer is 15%-25% of the total thickness of the high zirconium refractory material; The high-zirconium refractory material has a relative density of ≥98%, an open porosity of ≤0.4%, a bending strength of ≥600 MPa, and a critical thermal shock resistance temperature difference of ≥600°C.
2. A method for preparing the high zirconium refractory material according to claim 1, characterized in that: The preparation method comprises: Preparation of ZrO2- Al2O3 composite powder: wet ball milling multiple groups of ZrO2- Al2O3 composite powders with different proportions, drying and sieving to obtain the powders required for forming the surface layer, middle layer and transition layer of high zirconium refractory materials; Molding and sintering: The powder is filled into a mold by layer-by-layer powder spreading method, and then pressureless sintering is performed after molding by cold isostatic pressing; or, the powder is filled into a mold and sintered by hot pressing to obtain a dense ZrO2-Al2O3 gradient symmetrical structure refractory material.
3. The method for preparing a high zirconium refractory material according to claim 2, characterized in that: The liquid medium used in the wet ball milling is composed of a mixture of polyvinyl alcohol solution and anhydrous ethanol, wherein the volume proportion of the polyvinyl alcohol solution is 10-30 vol%; The amount of polyvinyl alcohol used is 0.5% to 1.5% of the weight of the ZrO2-Al2O3 composite powder; The wet ball milling process has a ball milling time of 10-18 h and a rotation speed of 100-200 r / min.
4. The method for preparing a high zirconium refractory material according to claim 2, characterized in that: The cold isostatic pressing pressure is 200-400 MPa, and the holding time is 2-5 min; The pressureless sintering temperature is 1550-1750°C, and the holding time is 2-4 hours; The hot pressing sintering is performed under a pressure of 30-70 MPa, a temperature of 1450-1700°C, and a heat preservation and pressure holding time of 1-3 h.
5. An application of the high zirconium refractory material according to claim 1, characterized in that: The high-zirconium refractory material is used for preparing a glass melting pool.
